Pseudomonas aeruginosa Biofilm Lifecycle: Involvement of Mechanical Constraints and Timeline of Matrix Production - Audrey David; Ali Tahrioui; Anne-Sophie Tareau; Adrien Forge; Mathieu Gonzalez; Emeline Bouffartigues; Olivier Lesouhaitier; Sylvie Chevalier (MDPI AG, 2024)
Pseudomonas aeruginosa is an opportunistic pathogen causing acute and chronic infections, especially in immunocompromised patients. Its remarkable adaptability and resistance to various antimicrobial treatments make it difficult to eradicate. Its persistence is enabled by its ability to form a biofilm. Biofilm is a community of sessile micro-organisms in a self-produced extracellular matrix, which forms a scaffold facilitating cohesion, cell attachment, and micro- and macro-colony formation. This lifestyle provides protection against environmental stresses, the immune system, and antimicrobial treatments, and confers the capacity for colonization and long-term persistence, often characterizing chronic infections. In this review, we retrace the events of the life cycle of P. aeruginosa biofilm, from surface perception/contact to cell spreading. We focus on the importance of extracellular appendages, mechanical constraints, and the kinetics of matrix component production in each step of the biofilm life cycle.